Photocatalytic Degradation of Gaseous Acetone by Photocatalysts with Visible Light and their Potential Applications in Painting - Yu-Hua Li; Sheng-Hua Yang; Chung-Shin Yuan; Huazhen Shen; Chung-Hsuang Hung (Aerosol and Air Quality Research)
Abstract Volatile organic compounds (VOCs) are air pollutants associated with health problem. Paints mixed with photocatalytic (PC) materials are considered to be effective in the removal of VOCs. Therefore, this investigation aimed to produce a novel visible induced photocatalyst component in paint. The synthesized photocatalysts (i.e., Ag-TiO2 and Fe-TiO2) were self-prepared by sol-gel method and further used to produce paints. The effects of the paints on VOC (i.e., acetone) degradation under the irradiation of visible light were tested in a batch PC reactor and an environmental chamber. In order to evaluate the control effect of VOCs using the paint, a si mulated test was conducted in a real room. The results of batch experiments showed that the degradation efficiencies of acetone by the paints were lower than that by the related photocatalysts. The paints made of 3% Fe-TiO2 and 1% Ag-TiO2 achieved the highest acetone degradation efficiency of 32.7 and 21.3%, respectively. The degradation test conducted in the environmental chamber indicated that the degradation efficiencies of acetone were 24.9, 46.2, and 32.4% for the paints made of TiO2, 3% Fe-TiO2 and 1% Ag-TiO2, respectively. It was evidently provided that the paint made of 3% Fe-TiO2 could effectively degrade organic pollutants in indoor environments.